Relationship between Stalk and Cob Mechanical Strength during the Late Growth Stage of Maize (Zea mays L.) - Jun Xue; Qun Wang; Hongyan Li; Yinghu Fan; Lulu Li; Ruizhi Xie; Keru Wang; Bo Ming; Peng Hou; Shaokun Li (Agronomy, 2020)
The stalk strength of maize (Zea mays L.) has a significant effect on stalk lodging and harvesting loss, and the cob mechanical strength affects the grain broken rate in mechanical grain harvesting. Clarifying the relationship between maize stalk strength and cob mechanical strength could provide a theoretical basis for the selection of cultivars with high lodging resistance and high suitability for mechanical grain harvesting. In 2017 and 2018, 64 maize cultivars were planted in four locations to investigate the changes in the bending strength of stalks and cobs using the three-point bending method during the late growth stage. The results showed that, in the late growth stage, with increasing number of days after physiological maturity, the stalk bending strength (SBS) of the fifth internode above the soil gradually decreased, the cob bending strength (CBS) decreased first and then increased, and it was lowest at about six to eight days after physiological maturity. In the same experimental site and sampling period, there was no significant correlation between the SBS and the CBS of different maize cultivars. Cluster analysis showed that most of the investigated maize cultivars showed low stalk strength during the late growth stage. However, a few of the maize cultivars were suitable for mechanical grain harvesting due to their characteristics of high stalk bending strength and moderate cob bending strength during the late growth stage.